การใช้สับปะรดเป็นตัวชี้วัดความเป็นพิษของโครเมียมและตะกั่วที่ปนเปื้อนในดิน - สุภาพร แป้งทา (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This study focus at using pineapple as an indicator for chromium and lead toxicity levels in contaminated soil. The primary experiment was conducted to study the concentration of chromium and lead that effect pineapple using 10 levels as follows: 100, 200, 400, 600, 800, 1,000, 1,500, 2,000, 2,500 and 3,000 milligram per kilogram. It was found that pineapples show toxicity at chromium concentration level of 1,500 milligram per kilogram and lead concentration level of 2,500 milligram per kilogram. In the experiment, solutions of chromium and lead were added at the level of 1,500 and 2,500 milligram per kilogram, respectively. Test groups were separated when pineapples were 30, 60, 90, 120, 150 and 180 days old. The harvesting occurred every 30 days after chemicals were added. Growth and toxicity of the plant were recorded. Samples of soil and pineapple, which was separated as parts above (trunk above the ground and leaves) and below (trunk below the ground and roots) the ground were collected. Then the amount of chromium and lead in pineapple and contaminated soil were analyzed. It was found that chromium and lead influence the growth of pineapple after 180 days of the experiment. They caused the slowest growth of pineapple. Dry weight of control group for parts above and below the soil were 56.46 and 24.57 grams, respectively. Dry weight of chromium added test group for parts above and below the soil were 41.64 and 14.71 grams, respectively. Dry weight of lead added test group for parts above and below the soil were 43.20 and 14.73 grams, respectively. From the study of chromium and lead accumulated in plant, it was found that the amount of accumulation increases as the duration of the experiment increases. The pineapple accumulated high amounts of both metals in parts below the soil throughout the 180 days of the experiment. The amount of chromium and lead accumulated in the plant were 7,356.67 and 6,177.00 milligram per kilogram, respectively. After 180 days of the experiment, it was found that chromium and lead toxicity was at their highest. The scores were 88.78 and 23.73 percent, respectively. This showed that chromium is more poisonous to pineapple than lead. Chromium caused withered leaves while lead caused yellow leaves. In addition, toxicity of both metals increased as the pineapple aged